Seismic design and analysis of underground structures - Hashash, Youssef M.A.; Hook, Jeffrey J.; Schmidt, Birger; I-Chiang Yao, John (Tunnelling and underground space technology, 2001)
Underground facilities are an integral part of the infrastructure of modern society and are used for a wide range of applications, including subways and railways, highways, material storage, and sewage and water transport. Underground facilities built in areas subject to earthquake activity must withstand both seismic and static loading. Historically, underground facilities have experienced a lower rate of damage than surface structures. Nevertheless, some underground structures have experienced significant damage in recent large earthquakes, including the 1995 Kobe, Japan earthquake, the 1999 Chi-Chi, Taiwan earthquake and the 1999 Kocaeli, Turkey earthquake. This report presents a summary of the current state of seismic analysis and design for underground structures. This report describes approaches used by engineers in quantifying the seismic effect on an underground structure. Deterministic and probabilistic seismic hazard analysis approaches are reviewed. The development of appropriate ground motion parameters, including peak accelerations and velocities, target response spectra, and ground motion time histories, is briefly described. In general, seismic design loads for underground structures are characterized in terms of the deformations and strains imposed on the structure by the surrounding ground, often due to the interaction between the two. In contrast, surface structures are designed for the inertial forces caused by ground accelerations. The simplest approach is to ignore the interaction of the underground structure with the surrounding ground. The free-field ground deformations due to a seismic event are estimated, and the underground structure is designed to accommodate these deformations. This approach is satisfactory when low levels of shaking are anticipated or the underground facility is in a stiff medium such as rock. Other approaches that account for the interaction between the structural supports and the surrounding ground are then described. In the pseudo-static analysis approach, the ground deformations are imposed as a static load and the soil-structure interaction does not include dynamic or wave propagation effects. In the dynamic analysis approach, a dynamic soil structure interaction is conducted using numerical analysis tools such as finite element or finite difference methods. The report discusses special design issues, including the design of tunnel segment joints and joints between tunnels and portal structures. Examples of seismic design used for underground structures are included in an appendix at the end of the report.